Detection of Slipped-DNAs at the Trinucleotide Repeats of the Myotonic Dystrophy Type I Disease Locus in Patient Tissues - Axford, Michelle M. (Public Library of Science, 2013)
Slipped-strand DNAs, formed by out-of-register mispairing of repeat units on complementary strands, were proposed over 55 years ago as transient intermediates in repeat length mutations, hypothesized to cause at least 40 neurodegenerative diseases. While slipped-DNAs have been characterized in vitro, evidence of slipped-DNAs at an endogenous locus in biologically relevant tissues, where instability varies widely, is lacking. Here, using an anti-DNA junction antibody and immunoprecipitation, we identify slipped-DNAs at the unstable trinucleotide repeats (CTG)n•(CAG)n of the myotonic dystrophy disease locus in patient brain, heart, muscle and other tissues, where the largest expansions arise in non-mitotic tissues such as cortex and heart, and are smallest in the cerebellum. Slipped-DNAs are shown to be present on the expanded allele and in chromatinized DNA. Slipped-DNAs are present as clusters of slip-outs along a DNA, with each slip-out having 1–100 extrahelical repeats. The allelic levels of slipped-DNA containing molecules were significantly greater in the heart over the cerebellum (relative to genomic equivalents of pre-IP input DNA) of a DM1 individual; an enrichment consistent with increased allelic levels of slipped-DNA structures in tissues having greater levels of CTG instability. Surprisingly, this supports the formation of slipped-DNAs as persistent mutation products of repeat instability, and not merely as transient mutagenic intermediates. These findings further our understanding of the processes of mutation and genetic variation.